2018
DOI: 10.1371/journal.pone.0203632
|View full text |Cite
|
Sign up to set email alerts
|

Molecular strain typing of the yaws pathogen, Treponema pallidum subspecies pertenue

Abstract: Yaws is a neglected tropical disease caused by the bacterium Treponema pallidum subspecies pertenue. The disease primarily affects children under 15 years of age living in low socioeconomic conditions in tropical areas. As a result of a renewed focus on the disease owing to a recent eradication effort initiated by the World Health Organization, we have evaluated a typing method, adapted from and based on the enhanced Centers for Disease Control and Prevention typing method for T. pallidum subsp. pallidum, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A subsequently introduced enhanced typing system included a portion of the TP0548 locus 33 . While the enhanced typing system has also been used for the typing of human TPE strains 12 , it did not overcome the difficulties associated with amplification of 60-bp repeats of the arp gene or the uncertainties associated with amplification of three different tpr -subfamily II genes in one single assay, followed by subsequent restriction enzyme analysis 11 . A recently published alternative method for MLST included the widely used TP0548 locus but also two additional loci located in the TP0136 and TP0326 genes 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequently introduced enhanced typing system included a portion of the TP0548 locus 33 . While the enhanced typing system has also been used for the typing of human TPE strains 12 , it did not overcome the difficulties associated with amplification of 60-bp repeats of the arp gene or the uncertainties associated with amplification of three different tpr -subfamily II genes in one single assay, followed by subsequent restriction enzyme analysis 11 . A recently published alternative method for MLST included the widely used TP0548 locus but also two additional loci located in the TP0136 and TP0326 genes 11 .…”
Section: Discussionmentioning
confidence: 99%
“…10 , subtype composition. Two recent studies suggested new typing systems for human yaws 11,12 . It was unclear though, whether the existing molecular typing systems for TPA or TPE of human origin can be applied to TP strains originating from NHPs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, methods for differentiating T. pallidum subspecies have been developed. These include a real-time PCR assay, nested PCR, a combination of PCR/RFLP analysis, and sequencing analysis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Since some yaws variants harbor a primer binding-site mutation, which tends to yield false-negative PCR results, molecular diagnosis in such a case should employ primers that are targeted towards highly conserved regions [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 16, 2019. ; https://doi.org/10.1101/2019.12.16.877886 doi: bioRxiv preprint tp0548 locus (nucleotides 130-212 according to tp0548 in the Nichols strain genome [AE 000520.1]) with published data, including a known TPA pattern and a known TPE pattern in silico, showed that the tp0548 genotype in the X-4 isolate was novel. The known tp0548 genotypes (a-ak) were assigned in a unique list containing TPA strains and TPE strains [20][21][22], and three other tp0548 genotypes of TPA strains were recently published: two were defined as type "r" and "s" by Grillová el al. [11], and one was defined as type "y" by Kumar et al [23].…”
Section: Classification Of the X-4 Isolatementioning
confidence: 99%